Navigating the complexities of hypertension: guidelines, screening and treatment approaches - Zaidi, Insia; Nag, Riya; Srivastava, Sanchita; Raza, Syed T.; Eba, Ale; Rizvi, Saliha; Fatima, Naseem; Khan, Farheen (International Journal of Research in Medical Sciences, 2024)
Hypertension or high blood pressure, is a prevalent condition and a leading cause of cardiovascular morbidity and mortality worldwide. This review provides an in-depth analysis of the current epidemiology, diagnosis and management of hypertension, with a focus on integrating guidelines from major health organizations such as the American College of Cardiology (ACC), American Heart Association (AHA) and European Society of Hypertension (ESH). Key factors contributing to primary and secondary hypertension are discussed, along with their respective diagnostic strategies. The review highlights the importance of accurate blood pressure measurement and the challenges posed by resistant hypertension. Moreover, it examines the disparities in hypertension management across various populations, underscoring the need for individualized care. A unique aspect of this review is the inclusion of telemedicine and digital healthcare solutions in the management of hypertension, particularly in the wake of the COVID-19 pandemic. Telehealth services, which have been increasingly integrated into primary care, offer significant potential for improving blood pressure control, especially in underserved and high-risk populations. The review concludes with a discussion on future directions in hypertension management, including advancements in remote monitoring and personalized treatment strategies. By synthesizing guideline-driven approaches and exploring innovative healthcare solutions, this review aims to provide healthcare professionals with a comprehensive understanding of the evolving landscape of hypertension diagnosis and management.